In vitro antioxidant activity of the methanolic extract of leaves of a hill tract plant Begonia roxburghii - Akter, Taslima; Nawar, Afra; Alam, Md Nur; Md Rafiquzzaman, - (Jahangirnagar University Journal of Biological Sciences, 2021)
The study was designed to investigate the antioxidant activities of the methanolic extract of leaves of Begonia roxburghii by five different in vitro methods namely Folin-Ciocalteu, total flavonoid content, phosphomolybdenum, total reducing power determination, and DPPH scavenging activity. Phenol content (Gallic acid equivalent) was found as 180.40±0.03 mg/g of the dry sample by the Folin-Ciocalteu method. Flavonoid assay method revealed the content of flavonoids (Quercetin equivalent) as 60.43±0.27 mg/g of the dry sample. Total antioxidant capacity of the extract was observed 243.43±0.11 mg/g ( ascorbic acid equivalent) by phosphomolybdenum method. Free radical scavenging activity (measured by the DPPH test) of the methanolic extract was found 158.36±0.22 μg/mL whereas ascorbic acid, the standard, showed 19.53±0.04 μg/mL. The methanolic extract of Begonia roxburghii leaves exhibited positive and linear dose dependent reducing power activity and its activity was comparable to the standard ascorbic acid for a given dose. Phytochemical screening of the extract showed positive results for alkaloids, carbohydrates, flavonoids, glycosides, saponins, steroids, and tannins, which demonstrate definite pharmacological actions on human body. The extract showed negative results for the steroids. Jahangirnagar University J. Biol. Sci. 9(1 & 2): 79-89, 2020 (June & December)